Applying TQM practices and service quality in higher education - Saberi, Nasarina; Romle, Abd Rahim; Romli, Siti Aishah; Muhamad Hussin, Nur Khairina; Muhammad Hussin, Zatun Najahah; Abdullah, Muhammad Syafiq (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Higher education sector has faced new paradigm of perspective in total quality management and service quality.Students is a main focus in higher education whereas they were assumed as customer focus because their satisfaction will be measured in order to ensure the quality is constantly improved. Thus, the implementation of TQM in higher education will be enhance to increasing of student satisfaction due to its success fullness in manufacturing. Hence, by applying TQM in higher education will lead to new environment in which students will feel satisfied and higher education able to serve the service as expected by student. Hence, this study is to explore total quality management practices in higher education towards service quality in context public university.